Creativity of physical education teachers from schools in Wroclaw - Guła-Kubiszewska, Halina; Starościak, Wojciech (Health Promotion & Physical Activity, 2017)
Introduction: It is possible to treat the competences of creative teachers of physical education as original activities or innovative activities – pedagogical innovation and creation. Researchers of creative personalities indicate a rich mosaic of features which have an effect on the creative attitude of a person. Such is represented by an individual with nonconformity and heuristic behaviour. The attitude towards nonproductive activity is characterized by algorithmic behaviour and conformist attitude. Objective: The aim of this study was to recognize the general creative potential among teachers of physical education working in secondary schools. Materials and methods: A survey was carried out in the school year 2013 / 2014 among teachers of physical education. 89 teachers including 52 woman and 37 men participated in the survey. Data collection was performed on the basis of diagnostic survey using questionnaires. A research tool used in the survey was the normative Creative Questionnaire Subscales for the KAHN-II behaviour, version for teachers ‘My ideal pupil – student’. Results and conclusions: Taking into consideration the unsatisfactory research results, it should be essential to make physical education teachers aware of their creative potential as well as the creative conditions which enable them to use their potential personally and efficiently.